Heart failure highlights in 2012–2013. (26th December 2013) - Liu, Licette C. Y.; Damman, Kevin; Lipsic, Eric; Maass, Alexander H.; Rienstra, Michiel; Westenbrink, B. Daan
Abstract : Heart failure has become the cardiovascular epidemic of the century. The European Journal of Heart Failure is dedicated to the advancement of knowledge in the field of heart failure management. In 2012 and 2013, several pioneering scientific discoveries and paradigm‐shifting clinical trials have been published. In the current paper, we will discuss the most significant novel insights into the pathophysiology, diagnosis, and treatment of heart failure that were published during this period. All relevant research areas are discussed, including pathophysiology, co‐morbidities, arrhythmias, biomarkers, clinical trials, and device therapy, including left ventricular assist devices.